Francisella tularensis live vaccine strain: proteomic analysis of membrane proteins enriched fraction - Pávková, Ivona; Hubálek, Martin; Zechovská, Jana; Lenco, Juraj; Stulík, Jirí (Proteomics, 2005)
Proteome analysis of Gram-negative facultative intracellular pathogen Francisella tularensis (F. tularensis) live vaccine strain has been performed only on whole-cell extracts so far. This is the first study dealing with the analysis of the membrane subproteome of this microorganism. A fraction enriched in membrane proteins obtained by carbonate extraction was separated using two-dimensional electrophoresis and all visualized spots were identified by mass spectrometry. The reference map is the basis for further comparative analyses of virulent and non-virulent F. tularensis strains.
Keywords: atenuované vakcíny; Electrophoresis, Gel, Two-Dimensional; membránové proteiny; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Proteomics; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Vaccines, Attenuated; Francisella tularensis; proteomika; Membrane Proteins; 2D gelová elektroforéza